A new evolutionary algorithm for sparse array optimization - Bardi, Francesco; Grimaccia, Francesco; Mussetta, Marco; Niccolai, Alessandro; Zich, Riccardo E. (2016 10th European Conference on Antennas and Propagation (EuCAP), 2016)
Evolutionary optimization is a growing field of research. The reasons of this growth are related with the flexibility of this optimization system that makes it usable in many fields of engineering. In this paper a new algorithm will be introduced: Leadership Based Optimization (LBO). This algorithm will be tested on the optimization of the array factor of a sparse array. This problem, due to the large number of variables and to its non-linearity is a good test case to assess the performance of the new algorithm.